Tracking oxytocin functions in the rodent brain during the last 30 years: From push‐pull perfusion to chemogenetic silencing. (11th March 2019) - Neumann, Inga D.; Landgraf, Rainer
Abstract : A short overview is provided of the last 30 years of oxytocin (and vasopressin) research performed in our laboratories, starting with attempts to monitor the release of this nonapeptide in the rodent brain during physiological conditions such as suckling in the lactating animal. Using push‐pull perfusion and microdialysis approaches, release patterns in hypothalamic and limbic brain regions could be characterised to occur from intact neuronal structures, to be independent of peripheral secretion into blood, and to respond differentially to various stimuli, particularly those related to reproduction and stress. Parallel efforts focused on the functional impact of central oxytocin release, including neuroendocrine and behavioural effects mediated by nonapeptide receptor interactions and subsequent intraneuronal signalling cascades. The use of a variety of sophisticated behavioural paradigms to manipulate central oxytocin release, along with pharmacological, genetic and pharmacogenetic approaches, revealed multiple consequences on social behaviours, particularly social fear.